Malaysia is a potential of Islamic finance hub: a comparative study on liquidity risk towards performance of both local and foreign Islamic banks / Innamul Hasan Zulkifli - Zulkifli, Innamul Hasan (Bachelor Of Business Administration (Hons) Marketing, 2015)
Following the aspiration of the Malaysian government in becoming a well-known Islamic finance hub, there are several foreign Islamic banks have been granted certain licenses to be operated in this country along with the dual system permitted by the Malaysian authorities within the local commercial banks. However, is this system and the existence of foreign Islamic banks will benefit to both financial institutions and government at large? In finance world, high risk, typically, associated with high return. Nevertheless, liquidity risk can be one of the serious issues that need to be properly addressed by the financial institutions. Therefore, this particular study is conducted in order to determine the level of liquidity risk among the Islamic banks established in Malaysia. All the samples of Islamic banks established in Malaysia were included in this study consisting of 10 local-owned and 6 foreign-owned. This research had applied multiple regressions in explaining the variation of bank’s performance by some the selected predictors related to the liquidity risk. Assumptions of normality, autocorrelation, heteroscedasticity and multicollinearity were tested for each dataset obtained from the financial statements before the estimations of the regression. These tests helped the researcher to come up with more credible results. The results found that all the predictors relating to the liquidity risk significantly affect the performance of the local-owned Islamic banks in Malaysia. However, this is contradict with the foreign-owned Islamic banks which there was only one variable of liquidity gap can explain the performance of the banks. It can be observed that local Islamic banks have better performance in overcoming NPLs with the sufficient amount of cash reserves while foreign Islamic banks have better performance of optimising liquidity gap in generating profit with lower risk of bankruptcy